SIMULTANEOUS MULTIELEMENT EXTRACTION WITH THE MEHLICH-1 SOLUTION FOR SOUTHERN BRAZILIAN SOILS DETERMINED BY ICP-OES AND THE EFFECTS ON THE NUTRIENTS RECOMMENDATIONS TO CROPS - Leandro Bortolon (Revista Brasileira de Ciência do Solo, 2010)
The amounts of macro (P, K, Ca and Mg) and micronutrients (Cu and Zn) extracted with the Mehlich-1 (M1) solution, by the 1.0 mol L-1 KCl (KCl) and with the 0.1 mol L-1 HCl (HCl) for representative soil types of the Rio Grande do Sul state (Brazil) were compared with those extracted with the Mehlich-1 solution determined with the inductively coupled plasma optical emission spectroscopy (ICP). The amounts of nutrients extracted by the different methods showed high correlation coefficients. On average, the Mehlich-1 solution extracted similar amounts of P, determined with colorimetric and ICP methods, and, K determined with emission and ICP. The amounts of Ca and Mg extracted with the Mehlich-1 solution, determined by ICP, were similar to those extracted with the KCl solution determined by the atomic absorption spectrophotometry. The amounts of Cu and Zn extracted with the Mehlich-1 solution, determined by the ICP, were higher than those extracted with the 0.1 mol L-1 HCl determined by the atomic absorption spectrophotometry. The results indicate that the Mehlich-1 solution and ICP can be used for simultaneous multielement extraction and determination for Southern Brazilian soils. However, a conversion factor for values interpretation is needed. The use of the conversion factor to determine the K availability index in soils is adequate and does not affect the K recommendations for crops in southern Brazilian soils.